Baseline mortality-adjusted survival in resected rectal cancer patients - Tarantino, Ignazio; Müller, Sascha A.; Warschkow, René; Kulu, Yakup; Schmied, Bruno M.; Büchler, Markus W.; Ulrich, Alexis (Journal of gastrointestinal surgery, 2014)
This investigation assessed the baseline mortality-adjusted 5-year survival after open rectal cancer resection.